Nano-engineered hydrocolloid-based delivery systems for natural flavonoids: From structural diversity to bioavailability enhancement and therapeutic applications - Yueming Wang; Amin Zhang; Wenjie Chu; Chengliang Qi; Tianxing Zhou; Yu Pan; Yuhan Wang; Chengyang Wang; Yuan Liu; Wenli Wang (Food Hydrocolloids, 2027)

Global drivers and pathways of mariculture maturation, 1997–2022 - Guo Yu; Yueming Liu; Xiaomei Yang; Yonglong Lu; Vincent Lyne; Zhihua Wang (Aquaculture, 2027)

Environmental regulation of sunken courtyards in standalone underground spaces: field measurements and ventilation-oriented design strategies - Yueming Wen; Meng Ouyang; Yitong Wang; Wenjie Peng; Chang Liu; Quan Jing; Yuchong Qian; Yuxuan Liu; Tongxin Guo; Hang Wei (Tunnelling and Underground Space Technology, 2026)

Spatial confinement in zeolites dominates pentene monomolecular cracking pathway - Fang Li; Weiyong Zhong; Min Sun; Yiran Wang; Penghe Zhang; Yueming Liu; Mingyuan He (Chemical Engineering Journal, 2026)

Decoupling natural ventilation and traffic noise in railway-adjacent dwellings: Field measurements and passive design strategies - Qi Zhao; Chen Chen; Meng Ouyang; Yitong Wang; Yueming Wen (Energy and Buildings, 2026)

Remote sensing and statistical data integration for spatial discrimination and mapping of mariculture products: A case study of Sansha Bay - Jie Jiang; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Dan Meng; Meiqi Zhou; Jialiang Liu (Ocean & Coastal Management, 2026)

Efficient identification of allergenic epitopes and analysis of the peptide recognition mechanism in tropomyosin of prawn (penaeus chinensis) through quantum chemistry computational framework - Xiangfei Hu; Qiannan Jiang; Hui Wang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2026)

High magnetic field-driven assembly of collagen peptide-cerium chelates from fish skin: Microstructure, colloidal stability and absorption behavior - Peihan Wu; Hui Wang; Yueming Hu; Pingwei Wen; Liang Zhang; Peng Zhang; Xiaomei Sha; Zongcai Tu (Food Hydrocolloids, 2026)

Nitrogen nutrition diagnosis of sweetpotato based on critical nitrogen dilution curve under different water conditions - Xu Zhao; Ximing Xu; Jing Yu; Minghuan Jin; Siyu Wang; Yueming Zhu; Guoquan Lu; Zunfu Lv (Irrigation Science, 2026)

Reactive heavy metals govern soil microbial communities: Depth-resolved evidence and disentangled metal-specific effects - Lixue Qiu; Chenle Wang; Fuxing Wu; Yueming Han; Lixun Zhang (Journal of Hazardous Materials, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Mechanistic insights into pulsed electric field-induced oxidative degradation of arginine and glutamic acid: Combined experimental characterization and DFT computation - Xiangfei Hu; Qiannan Jiang; Zongcai Tu; Yueming Hu; Hui Wang (Food Research International, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Torque teno virus in the lower respiratory tract: association with immunosuppression but not mortality in severe pneumonia—a multicenter retrospective cohort study - Xian Zhang; Lifei Chen; Fang Wang; Xiaofang Xu; Yueming Wu; JunLong Xu; Yongan Xu; Xuwei He (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Transforming from ‘natural tools’ into ‘custom sensors’: combining directionally designed biological nanopore electrochemistry sensing lumens with AI-driven analytics to pioneer a new paradigm for food analysis - Yanyang Yu; Yongfei Deng; Zhiyong Cui; Yueming Wang; Chenxi Zhang; Jinna Wang; Danni Zhang; Tianxing Zhou; Chuyue Gong; Shengli Zhang (Trends in Food Science & Technology, 2026)

High-throughput characterization of local structural imperfections in freestanding oxide membranes by lock-in thermography - Ao Wang; Jinfeng Zhang; Jinxiang Yan; Fang Xu; Qing Wang; Yueming Huang; Minghui Fan; Qiming Lv; Zhengguo Liang; Kunjie Dai; Dazhi Hou; Wenbin Wu; et al. (Science Bulletin, 2026)

A hybrid MIMO-CNN-BiLSTM-AM model for efficient prediction of motion responses and mooring tension of FOWTs - Xiaojie Tian; Xiaolong Wang; Zhi Li; Yueming Zheng; Wei Deng (Ocean Engineering, 2026)

Dynamic patterns of constraints, drivers and impacts of land-based aquaculture areas and their implications: A case of Guangdong, China from 1990 to 2020 - Ku Gao; Xiaomei Yang; Zhihua Wang; Yueming Liu; Feilin Lai; Junyao Zhang (Land Use Policy, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

In-situ constructed Ag/CNT hierarchical networks in TPU nanofibers for dual-mode triboelectric sensing - Shiqiang Ouyang; Feijie Wang; Yichi Liu; Suyang Wang; Yaoli Wang; Yuefan Liu; Zhixuan Mei; Kaixin Liao; Shenzhuo Zhang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Online monitoring of deposit-induced corrosion in a Waste-to-Energy boiler - Wenjie Liu; Yafang Wang; Yan Wang; Yongjun Liu; Anming Du; Qiongyu Ren; Xinran Zheng; Xiyu Chen; Minmin Zhou; Yueming Wang; Lunbo Duan (Waste Management, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

An on-tissue parallel d0/d20-meladrazine derivatization approach for fatty acid peroxidation products imaging in adult zebrafish - Ji Yang; Yue Sun; Yueming Li; Zhonghua Wang; Zeper Abliz; Zhi Zhou (Analytica Chimica Acta, 2026)

Spatiotemporal heterogeneity of human footprint across China's coastal zone: Integrating geomorphic and policy drivers - Dan Meng; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Ku Gao (Ocean & Coastal Management, 2026)

Engineering design paradigms for high-performance rotating triboelectric nanogenerators: From structural optimization to system synergy - Yan Ma; Feijie Wang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

A Remote Sensing Monitoring System for Marine Red Tides Based on Targeted Negative Sample Selection Strategies - Qichen Fan; Yong Liu; Yueming Liu; Xiaomei Yang; Zhihua Wang (Journal of Marine Science and Engineering, 2026)
The monitoring of harmful algal blooms (HABs) constitutes a vital component of marine environmental protection and the sustainable development of the marine economy. However, the highly dynamic nature of these small targets, compounded by the complex water color interference prevalent in the coastal waters where HABs frequently occur, has resulted in traditional remote sensing monitoring methods, particularly those relying on fixed spectral index thresholds and pixel-wise binarization, suffering from imprecise identification in turbid coastal waters where suspended sediments, cloud cover, and sun glint create spectral confusion. These methods also exhibit low automation due to manual threshold adjustment requirements and poor transferability across different spatiotemporal conditions. Consequently, these methods struggle to meet practical application requirements. This study establishes a U-net model-based remote sensing identification framework for red tides using HY-1D CZI imagery (50 m resolution, 1–3 day revisit), targeted negative sample strategies, and event-level accuracy validation methods to achieve efficient marine red tide detection. Targeted negative sample selection involves purposefully selecting spectrally ambiguous regions as negative samples, aiming to enhance recognition accuracy and sample selection efficiency. The combination of targeted sampling with deep learning enables portability to new spatiotemporal contexts by learning invariant spectral–spatial features rather than relying on scene-specific thresholds. Experimental results demonstrate that the targeted negative sample strategy reduces event-level model false negatives by 27%, false positives by 36%, and increases the F1 score by 0.3217. Using an identical sample size, the targeted sample selection strategy yields an F1 score 0.0479 higher than random sampling. To achieve equivalent recognition accuracy, an increased number of random samples would be required. Comparative experiments reveal that the proposed method enhances sample selection efficiency by 87.5%. Transferability is demonstrated through successful identification of red tide patches in Wenzhou waters on 13 April 2022, without model retraining. This demonstrates that red tide remote sensing recognition based on targeted sample selection enables efficient, precise, and automated identification without human intervention, providing a reliable technical solution for operational marine red tide monitoring.

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Non-linear interaction behavior of mixed industrial solid wastes in circulating fluidized beds: Reacting MP-PIC simulation - Minmin Zhou; Xiuzhi Wang; WenQiang Chen; Qiuchen Sun; DongFu Wang; Zhijiang Han; Chenxi Lu; Yueming Wang; Lunbo Duan; Wojciech P. Adamczyk (Fuel, 2026)

Quantifying the spatiotemporal characteristics and driving mechanisms of greenhouse gas emissions from the wastewater treatment sectors in Chinese cities - Xiaona Wang; Yueming Gao; Nana Zhao (Environmental Research, 2026)

Total replacement of soy with alternative plant-based ingredients, feed enzymes and a probiotic in a mixed-cereal broiler diet fed during an entire growth cycle - Yueming Dersjant-Li; Abiodun Bello; Leon Marchal; Qiong Wang; Kirsty Gibbs; Jos.G.M. Houdijk (Animal Feed Science and Technology, 2026)

Electrochemical insights into the High-Temperature corrosion mechanism of 12Cr1MoV steel under Chlorine-Rich conditions - Yafang Wang; Wenjie Liu; Minmin Zhou; Wenxiu Yang; Dongfu Wang; Yueming Wang; Lunbo Duan (Fuel, 2026)

Effect of strong reducing atmosphere on mineral transformation in high-iron and high-calcium coal during plasma underground coal gasification - Chuan Qi; Weibin Wang; Jiahong Cao; Xiongchao Lin; Yueming Liu; Shuqin Liu (Fuel, 2026)

Analytical solution for transient groundwater flow to partially penetrated waterproof curtains in unconfined aquifers - Qian Wang; Jiangwei Zhang; Enze Ma; Yueming Qi; Liyang Xu; Yue Fan; Xiuyu Liang (Journal of Hydrology, 2026)

Corrigendum to “Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach” [J Hazard Mater 501 (2026) 14065] - Kashif Ali Memon; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Simultaneous removal of Mn²⁺ and Sr²⁺ from wastewater via microbially induced carbonate precipitation (MICP) using immobilized Bacillus licheniformis K-1: A sustainable bioremediation approach - Memon Kashif Ali; Huaxiao Yan; Muhammad Mujahid; Jiabin Geng; Shuqi Wang; Runxi Yin; Yueming Zhao; Akash Kumar; Azhar Ali Laghari; Zuozhen Han; Na Guo; Hui Zhao (Journal of Hazardous Materials, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

Corrigendum to “Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit” [Postharvest Biol. Technol. 224 (2025) 113466] - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Insight into the pollution potential of different ecological types of lakes from the perspective of dissolved organic matter characteristics: Field and experimental evidence - Yang Deng; Longmian Wang; Yueming Zhu; Xiang Zhu; Qingqing Pang; Yuying Ma; Fuquan Peng; Lei Xie; Xiaoguang Xu; Qiu Jin; Guoxiang Wang; Fei Yang; et al. (Journal of Hydrology, 2025)

High magnetic field-assisted preparation of food-derived collagen peptide-cerium (III) chelate: reducing oxidative stress and helping restore osteoblast function - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu (Food Bioscience, 2025)

Effect of phenolic hydrogen on the formation of chitosan -prenylated flavonoids nanocomplexes - Jinping Wang; Jiawen Chen; Yueming Jiang; Bao Yang; Lingrong Wen (Food Hydrocolloids, 2025)

Montmorillonite-derived Mg-doped NaAlSiO4 for radiative cooling applications - Zhizheng Xiang; Zhongqiu Tong; Haowei Yang; Jie Yu; Yingjun Xiao; Yueming Wang; Shaoyuan Li; Xingang Li; Mikhail M. Mikhailov; Wenhui Ma (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Astragaloside IV improves the quality of in vitro postovulatory aged oocytes by decreasing oxidative stress in mice - Yueming Wang; Yu Wang; Yashi Fan; Fanglin Xiang; Yuechan Wang; Jinmei Cheng (Theriogenology, 2025)

Molecular mechanisms of superheated steam-induced modifications enhancing ovalbumin functional properties: Insights from site identification and peptidomic analysis - Haiqi Chen; Zuohua Xie; Feifei Wang; Zongcai Tu; Pingwei Wen; Siqiong Zhang; Hui Wang; Yueming Hu (Food Chemistry, 2025)

Modulating immune reactivity of grass carp parvalbumin via pulsed electric field-induced variation of structural properties - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Yueming Hu; Zongcai Tu (Food Chemistry, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Bioinspired graphene-based aerogel polyurethane multifunctional coatings with high-temperature resistance, anti-corrosion and anti-fouling properties - Yuping Liu; Limei Tian; Jie Zhao; Jiarun Tian; Yueming Wang; Jiyu Sun (Chemical Engineering Journal, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

Investigation of the mechanism of H2O2 combined pulsed electric field treatment reducing the antigenicity of parvalbumin and tropomyosin by high-resolution mass spectrometry, molecular dynamics and DFT computation - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Jie Cheng; Haibin Liu; Yueming Hu; Zongcai Tu (Innovative Food Science & Emerging Technologies, 2025)

The effects of gradient magnetic field on the detailed flow behavior of diffusion flames: Application for stabilizing coal bed methane flames - Hetong Gao; Yueming Wang; Minmin Zhou; Lunbo Duan (Fuel, 2025)

Chelation of cerium (III) with fish skin collagen peptides: Improving the in vitro stability and bioavailability of inorganic cerium - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu; Jie Cheng; Hai-bin Liu; Pingwei Wen (Food Research International, 2025)

MOFs-derived FeNi bimetallic phosphide with tightly coupled heterogeneous interface for PMS activation - Xiaoyang Liu; Yueming Zhu; Minghui He; Chenyu Zhang; Gancheng Zuo; Yuting Wang; Shaogui Yang; Huan He (Chemical Engineering Journal, 2025)

The impact of land use on the composition of dissolved organic matter and its relationship with microbes in a river basin in Northwestern China: Insights into microbial community structure and metabolic function - Xiang Zhu; Xinhua Gao; Yueming Zhu; Jingjie Huang; Fuquan Peng; Qingqing Pang; Fei Yang; Lei Xie; Zulin Hua; Longmian Wang (Journal of Environmental Management, 2025)

Phase congruency image mosaicking approach for aerial mid-wave infrared low-overlap array scanning images - Jiani He; Yueming Wang; Lixia Deng; Yitao Li; Zhao-Liang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

In vivo cell migratory behavior drives therapeutic efficacy evidenced by SWIR fluorescence imaging - Huizhu Li; Xiao Zhang; Shunyao Li; Yueming Wang; Shingo Ogura; Kemeng Shao; Xiner Du; Yan Wo; Shiyi Chen; Jun Chen; Xuanfeng Qin; Yunxia Li; et al. (Chemical Engineering Journal, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Responses of microbial community to different depths in volcanic soils of Nvshan Volcano - Jin Chen; Haining Wang; Ye Cui; Yiming Dai; Yueming Bao; Rui Qin; Qixiu Cheng; Xiaoyu Li (World Journal of Microbiology and Biotechnology, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Synergistic impact of plant essential oil based microemulsion on lychee preservation in comparison to Prochloraz - Yujie Shen; Xin Zhou; Jupeng Zhao; Zhe Wang; Dandan Zhang; Lingrong Wen; Yueming Jiang; Liang Gong (Sustainable Chemistry and Pharmacy, 2025)

Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

The role of SYK phosphorylation in LPS-induced immunoglobulin responses of B cells in large yellow croaker (Larimichthys crocea) - Hongjun Xie; Shuangshuang Cao; Yueming Chen; Zhiqiang Wang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

MAPK signaling mediated intestinal inflammation induced by endoplasmic reticulum stress and NOD2 - Siyuan Peng; Yan Zhao; Wang Jiang; Yan Long; Tian Hu; Mengling Li; Jinyue Hu; Yueming Shen (Molecular and Cellular Biochemistry, 2025)

Remaining useful life prediction of lead-acid battery using multi-phase wiener process-based degradation model - Jun Yang; Yueming Hong; Wenlin Wang; Guohua Wu (Process Safety and Environmental Protection, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Construction of W/O/W microcapsules based on the combination of polyglycerol polyricinoleate/protein for the co-encapsulation of crocin and quercetin: Physical properties, stability and in vitro digestion - Wei Fan; Yan Shi; Yueming Hu; Shu Wang; Jing Zhang; Wei Liu (Food Chemistry, 2025)

Spatial extraction of sea-cucumber aquaculture ponds using remote sensing spectral and temporal features - Ruoqi Du; He Li; Chong Huang; Qingsheng Liu; Yueming Liu; Zhihua Wang (Frontiers in Marine Science, 2025)
The spatial distribution of aquaculture ponds plays a critical role in the layout, management, and evaluation of the aquaculture industry. While extensive research has been conducted on aquaculture pond extraction and monitoring, studies focusing on the differentiation of aquaculture ponds by species remain limited. The similar shapes and spectral features of water bodies associated with different species pose a challenge for extraction. A method for extracting sea-cucumber aquaculture ponds is proposed based on spectral temporal features using Sentinel-2 satellite imagery in this study. The method involves selecting the optimal sensitive spectral bands or combinations to construct two remote sensing indices of land-based aquaculture ponds. Using a time-series dataset of these indices, three key features—the mean and two slopes—are extracted. The corresponding time windows and thresholds for these key features are identified to develop a decision-tree algorithm for extracting sea-cucumber ponds. This method was applied to coastal aquaculture zones in Liaoning Province, China, to identify the spatial distribution of sea-cucumber aquaculture ponds in 2016 and 2023. The results showed that: (1) the proposed method achieved high extraction accuracy, with an overall accuracy of 79.24%; (2) Total area of sea-cucumber ponds in Liaoning Province was 931.08 km 2 , primarily located along the Huludao Xingcheng-Jinzhou Linghai and Yingkou Xishi-Dalian Zhuanghe coastal zones; (3) Over the past seven years, the area of sea-cucumber ponds increased by 624.57 km 2 , with expansion concentrated on the northwest coast of Liaodong Bay and both the eastern and western sides of the Liaodong Peninsula. These findings provide scientific support for the sustainable development of sea-cucumber aquaculture.

Mapping of Rsn2, a locus conferring rice tolerance to toxin from the causal agent of rice sheath blight Rhizoctonia solani - Xiang Xue; Yu Wang; Yueming Xu; Yumei Zhang; Fang Gu; Yuyin Ma; Zongxiang Chen; Yafang Zhang (Journal of Plant Pathology, 2025)

Freezing or searing: Unraveling the impact of extreme temperatures on poverty in China - Huiming Zhang; Shuyuan Wang; Kai Wu; Yueming (Lucy) Qiu; Shouyang Wang; Yongfan Zhao (Environmental Impact Assessment Review, 2025)

Porous spherical g-C3N4/geopolymer composite for photo-Fenton-like degradation of tetracycline hydrochloride - Yutong Song; Xiaohong Zhang; Chengying Bai; Wei Peng; Yueming Ren; Xiaodong Wang; Ting Zheng; Paolo Colombo; Bin Wang (Journal of Water Process Engineering, 2025)

Mechanism studies of gliadin-glucose glycation reaction and products formation by heat treatment with different conduction modes - Qiannan Jiang; Xiangfei Hu; Zongcai Tu; Pingwei Wen; Yueming Hu; Siqiong Zhang; Hui Wang; Zuohua Xie (Food Chemistry, 2025)

Higher dynamic and turnover yet enhanced organic carbon burial in Spartina alterniflora sediments: A case study in a temperate coastal wetland - Yueming Wu; Beiyun Xu; Danqing Sun; Shan Jiang; Jian Li; Yiyun Wang; Ying Wu (CATENA, 2025)

Progress in Preparation Technology and Functional Research On Marine Bioactive Peptides - Jing Wang; Fengcheng Li; Wenjun Li; Yueming Li; Jian Zhang; Song Qin (Marine Biotechnology, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Modulating allergenicity of prawn tropomyosin (penaeus chinensis) via pulsed electric field-induced conformational changes - Xiangfei Hu; Hui Wang; Yueming Hu; Pingwei Wen; Xiongchen Wu; Zongcai Tu (Food Chemistry, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Development of an integrated online deposition and corrosion monitoring system in a full-scale solid waste CFB boiler - Yueming Wang; Jinghui He; Yuxing Wang; Feiyue Sun; Chenxi Lu; Shuo Zhang; Lunbo Duan (Waste Management, 2024)

Review the antioxidant and angiotensin converting enzyme inhibitory peptides derived from fish: Preparation, structure-relationship, bioavailability and ameliorating strategies - Shu Wang; Lu Zhang; Hui Wang; Bizhen Zhong; Yueming Hu; Hongmei Yin; Zongcai Tu (Food Bioscience, 2024)

Magnetic field: A non-thermal technology in food processing - Shu Wang; Lu Zhang; Hui Wang; Wei Fan; Yueming Hu; Zongcai Tu (Food Control, 2024)

Sustainable utilization of cultivated land resources based on "element coupling-function synergy" analytical framework: A case study of Guangdong, China - Hao Yang; Runyan Zou; Yueming Hu; Lu Wang; Yingkai Xie; Zhengxi Tan; Zhiqiang Zhu; A.-Xing Zhu; Jianzhou Gong; Xiaoyun Mao (Land Use Policy, 2024)

A Tank Experiment of the Autonomous Detection of Seabed-Contacting Segments for Submarine Pipelaying Operations - Bo Wang; Jie Wang; Chen Zheng; Ye Li; Jian Cao; Yueming Li (Journal of Marine Science and Engineering, 2024)
Due to the weak structural features of pipelines and underwater light attenuation, the complex and harsh environment of the seabed greatly increases the possibility of an underwater autonomous remotely operated vehicle losing a detected seabed-contacting segment during pipe-laying operations. To address this problem, we propose a cascade attention module and a prefusion module with a convolutional neural network. The cascade attention module samples the feature maps in a non-convolutional form to realize the interaction between structure and channels, and the attention map is generated by cascading attention. The prefusion module pre-fuses the three layers of feature maps from different stages in the backbone, and the delicate features of the shallow feature maps are fused with the deeper feature maps to generate richer feature maps with space location and semantic classification information. We conduct experiments to verify our modules, both on the underwater pipeline dataset and in a tank test. The results show that our modules can improve the performance of different neural network models for seabed-contacting segment detection. The target detection and instance segmentation performance of the best model is improved through a 6.3% increase in AP and a 3.8% increase in mean intersection over union compared with the baseline model.

Application of multilevel immobilized carbon nanotube/sulfur doped carbon nitride composite photocatalytic coating for Cr6+(aq.) reduction - Zhenyu Shi; Lei Rao; Peifang Wang; Yueming Yu (Chemical Engineering Journal, 2024)

Size-dependent growth strategy and allometry, but not complementarity, as major drivers of fine-root biomass and productivity across warm-temperate forests - Wenhao Miao; Zijian Guo; Yueming Lyu; Xuemei Wang; Xiangping Wang (European Journal of Forest Research, 2024)

The effect of artificial intelligence evolving on hyperspectral imagery with different signal-to-noise ratio, spectral and spatial resolutions - Jianxin Jia; Xiaorou Zheng; Yueming Wang; Yuwei Chen; Mika Karjalainen; Shoubin Dong; Runuo Lu; Jianyu Wang; Juha Hyyppä (Remote Sensing of Environment, 2024)

Unravelling the morphology effect of Pt/In2O3 catalysts for highly efficient hydrogen production by methanol steam reforming - Lini Liao; Yong Men; Yueming Wang; Shuyi Xu; Shuya Wu; Jinguo Wang; Zhenrong Yan; Xuelong Miao (Fuel, 2024)

Acid strength controlled reaction pathways of propylene conversion under olefin cracking conditions over ZSM-5 - Qin Zhao; Fang Li; Yiran Wang; Yueming Liu; Mingyuan He (Fuel, 2024)

Insight into the effects of pulsed electric field on the structure, aggregation characteristics and functional properties of whey proteins - Xiangfei Hu; Hui Wang; Yueming Hu; Zongcai Tu (Food Hydrocolloids, 2024)

Insight into the aroma and taste enrichment pattern in Chinese traditional braised soup based on HS-SPME-GC-MS and HS-GC-IMS - Feifei Wang; Debin Guo; Pingwei Wen; Haiqi Chen; Yueming Hu; Jun Li; Zongcai Tu; Hui Wang (Food Bioscience, 2024)

Lead exposure induces neurodysfunction through caspase-1-mediated neuronal pyroptosis - Dongjie Peng; Leilei Wang; Yuanyuan Fang; Lili Lu; Zhaocong Li; Siyang Jiang; Jing Chen; Michael Aschner; Shaojun Li; Yueming Jiang (Environmental Research, 2024)

Environmental protection tax and corporate carbon emissions in China: a perspective of green innovation - Rongrong Wei; Mengling Wang; Yueming Xia (Clean Technologies and Environmental Policy, 2024)

A Method for Multi-AUV Cooperative Area Search in Unknown Environment Based on Reinforcement Learning - Yueming Li; Mingquan Ma; Jian Cao; Guobin Luo; Depeng Wang; Weiqiang Chen (Journal of Marine Science and Engineering, 2024)
As an emerging direction of multi-agent collaborative control technology, multiple autonomous underwater vehicle (multi-AUV) cooperative area search technology has played an important role in civilian fields such as marine resource exploration and development, marine rescue, and marine scientific expeditions, as well as in military fields such as mine countermeasures and military underwater reconnaissance. At present, as we continue to explore the ocean, the environment in which AUVs perform search tasks is mostly unknown, with many uncertainties such as obstacles, which places high demands on the autonomous decision-making capabilities of AUVs. Moreover, considering the limited detection capability of a single AUV in underwater environments, while the area searched by the AUV is constantly expanding, a single AUV cannot obtain global state information in real time and can only make behavioral decisions based on local observation information, which adversely affects the coordination between AUVs and the search efficiency of multi-AUV systems. Therefore, in order to face increasingly challenging search tasks, we adopt multi-agent reinforcement learning (MARL) to study the problem of multi-AUV cooperative area search from the perspective of improving autonomous decision-making capabilities and collaboration between AUVs. First, we modeled the search task as a decentralized partial observation Markov decision process (Dec-POMDP) and established a search information map. Each AUV updates the information map based on sonar detection information and information fusion between AUVs, and makes real-time decisions based on this to better address the problem of insufficient observation information caused by the weak perception ability of AUVs in underwater environments. Secondly, we established a multi-AUV cooperative area search system (MACASS), which employs a search strategy based on multi-agent reinforcement learning. The system combines various AUVs into a unified entity using a distributed control approach. During the execution of search tasks, each AUV can make action decisions based on sonar detection information and information exchange among AUVs in the system, utilizing the MARL-based search strategy. As a result, AUVs possess enhanced autonomy in decision-making, enabling them to better handle challenges such as limited detection capabilities and insufficient observational information.

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

The unequal impacts of extremely high temperatures on households’ adaptive behaviors: Empirical evidence from fine-grained electricity consumption data - Han Shi; Bo Wang; Yueming Lucy Qiu; Nana Deng; Baichen Xie; Bin Zhang; Shijun Ma (Energy Policy, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Free and Forced Vibration Characteristics of a Composite Stiffened Plate Based on Energy Method - Xin Gu; Xianzhong Wang; Weiguo Wu; Jie Sun; Yongshui Lin; Yueming Fang (Journal of Marine Science and Engineering, 2024)
The composite stiffened plate has garnered significant attention in the lightweight design of ship structures due to its superior mechanical properties. Although it reduces the structural weight, it also increases vibration sensitivity. Thus, investigating the vibration characteristics of the composite stiffened plate is crucial. This paper proposed a theoretical model based on the energy principle and the improved Fourier series method (IFSM) to analyze the composite stiffened plate vibration characteristics. The model demonstrates high reliability and accuracy, as confirmed through convergence analysis and comparison with experimental results from the published literature. Results indicate that geometry and material parameters significantly impact the natural frequency and can mitigate vibration responses by increasing thickness and stiffness. Additionally, ply design parameters markedly influence the vibration of composite stiffened plates, enhancing low-frequency vibration performance through optimal ply design. The structural parameters of the stiffeners, particularly the height and number of stiffeners, play a crucial role, enhancing stiffness and reducing the vibration responses of the composite stiffened plates.

A new curve of critical leaf nitrogen concentration based on the maximum root dry matter for diagnosing nitrogen nutritional status of sweetpotato - Zhi Zhang; Ximing Xu; Minghuan Jin; Jiacheng Bai; Xing Shu; Lijuan Deng; Siyu Wang; Yueming Zhu; Yuheng Liu; Guoquan Lu; Zunfu Lv (European Journal of Agronomy, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

Evaluation of coastal zone development and utilization considering natural ontology, a case study in Liaoning Province, China - Guo Yu; Zhihua Wang; Yueming Liu; Xiaomei Yang; Junyao Zhang; Ku Gao (Ocean & Coastal Management, 2024)

Efficient preparation of oyster hydrolysate with aroma and umami coexistence derived from ultrasonic pretreatment assisted enzymatic hydrolysis - Junwei Zhang; Zongcai Tu; Zizi Hu; Yueming Hu; Hui Wang (Food Chemistry, 2024)

Insight into the molecular mechanism underlying the enhancement of antioxidant activity in ovalbumin by high-energy electron beam irradiation - Haiqi Chen; Zhongyue Bian; Pingwei Wen; Hui Wang; Yueming Hu; Zongcai Tu; Guangxian Liu (Food Chemistry, 2024)

Discrimination and characterization of different ultrafine grinding times on the flavor characteristic of fish gelatin using E-nose, HS-SPME-GC-MS and HS-GC-IMS - Jinghong Xu; Zongcai Tu; Hui Wang; Yueming Hu; Pingwei Wen; Xiaoliang Huang; Shu Wang (Food Chemistry, 2024)

Mn2+ recycling in hypersaline wastewater: unnoticed intracellular biomineralization and pre-cultivation of immobilized bacteria - Huaxiao Yan; Shengping Jin; Xiaolei Sun; Zuozhen Han; Hongmei Wang; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; Lirong Wei; et al. (World Journal of Microbiology and Biotechnology, 2024)

Water quality and microecosystem of water tanks in karst mountainous area, Southwest China - Qigang Wang; Guanghui Jiang; Ziyong Sun; Yueming Liang; Fan Liu; Jie Shi (Environmental Science and Pollution Research, 2024)

The decrease of Ara h 2 allergenicity by glycation is determined by reducing sugar chain length and isomers - Ping Yang; Xumei Wang; Hui Wang; Yueming Hu; Pingwei Wen; Zongcai Tu (Food Chemistry, 2024)

Trajectory-Following Control of an Unmanned Aerial–Aquatic Vehicle under Complex Coupling Interferences - Jian Cao; Jiayuan Mao; Yueming Li; Le Wang; Biao Cao (Journal of Marine Science and Engineering, 2023)
This article explores trajectory-following control for an unmanned aerial–aquatic vehicle (UAAV) navigating complex ocean disturbances and the interplay of air–seawater coupling factors. First, leveraging the backstepping technology, an adaptive algorithm is proposed to tackle the attitude and position following. Additionally, a nonlinear observer is crafted to estimate complex ocean disturbances. The UAAV model, characterized by six degrees of freedom (DOF) and nonlinear properties, experiences significant pose changes when emerging from water, underscoring the critical importance of precise pose control. Finally, stability analysis and numerical simulations are demonstrated to verify the feasibility and validity of the proposed control strategies.

Transmedia Performance Research and Motion Control of Unmanned Aerial–Aquatic Vehicles - Xiangren Sun; Jian Cao; Yueming Li; Haipeng Li; Weikai Wang (Journal of Marine Science and Engineering, 2023)
This paper presents an improved motion controller based on the backstepping method to address nonlinear control challenges in unmanned aerial–aquatic vehicles (UAAVs), enabling them to navigate between two different media. The nonlinear control approach is applied to UAAV motion control, incorporating filters to improve stability. The study designs motion controllers for three UAAV phases: underwater, in the air, and transitioning between media. Fluid simulations of the emergence process of the UAAV for future field experiments were conducted. By fine-tuning the simulations, a comprehensive understanding of the vehicle’s performance is obtained, offering crucial insights for the development of subsequent control systems. Simulation results confirm the controller’s ability to achieve target trajectory tracking with control system responses that meet practical requirements. The controller’s performance in attitude control and trajectory tracking is verified in underwater gliding, transmedia transitions, and airborne phases, demonstrating its effectiveness.

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

Insight into the crack characteristics and mechanisms of retrogressive slope failures: A large-scale model test - Yueming Yin; Qinglu Deng; Weibo Li; Kai He; Zhenghong Wang; Haijun Li; Pengju An; Kun Fang (Engineering Geology, 2023)

Coupling strength between omnivory loops and their one-species-delete subloops drives real food web stability - Jianfeng Feng; Shengpeng Li; Xiaoxiao Li; Yueming Jiang; Ruyue Wang; Xianhao Meng; Wei Yang; Tao Sun; Peter C. de Ruiter; Yongtang Shi; Nils Chr. Stenseth (Theoretical Ecology, 2023)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Changes in the spatial distribution of mariculture in China over the past 20 years - Yueming Liu; Zhihua Wang; Xiaomei Yang; Shaoqiang Wang; Xiaoliang Liu; Bin Liu; Junyao Zhang; Dan Meng; Kaimeng Ding; Ku Gao; Xiaowei Zeng; Yaxin Ding (Journal of Geographical Sciences, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

In-situ measuring and predicting dynamics of soil bulk density in a non-rigid soil as affected by tillage practices: Effects of soil subsidence and shrinkage - Yuekai Wang; Zhongbin Zhang; Zichun Guo; Yueming Chen; Junsheng Yang; Xinhua Peng (Soil and Tillage Research, 2023)

H2O2-activated transcription factor MdERF4 negatively regulates ethylene biosynthetic during fruit ripening by suppressing MdACS1 transcription - Nannan Zang; Xiaojing Li; Liyong Qi; Zhuoran Zhang; Yueming Yang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2023)

Underwater object tracker: UOSTrack for marine organism grasping of underwater vehicles - Yunfeng Li; Bo Wang; Ye Li; Zhuoyan Liu; Wei Huo; Yueming Li; Jian Cao (Ocean Engineering, 2023)

Revealing the crystal phase effect of CeO2 in spinel-based nanocatalysts toward the peroxymonosulfate activation for organics degradation - Yuxuan He; Yueming Zhu; Jin Qian; Peifang Wang; Yuhang Zhang; Kailin Xu; Bianhe Lu; Yin Liu; Junwei Shen (Chemical Engineering Journal, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

Source Apportionment of Soil Heavy Metal(Loid)s in Farmland Using Diverse Models: A Comparative Assessment in the Yellow River Delta - Wei Huang; Shuhuan Wang; Lu Wang; Yingqiang Song; Yue Zhu; Hao Yang; Yingkai Xie; Yueming Hu (Journal of Marine Science and Engineering, 2023)
The rapid development of industrialization and urbanization has posed serious challenges for coastal farmland ecosystems. Source apportionment of soil heavy metals is an effective way for the detection of non-point source pollution in farmland to help support the high-quality development of coastal agriculture. To this end, 113 surface soil samples were collected in the coastal delta of China, and the contents of As, Cd, Cr, Cu, Ni, Pb, and Zn were determined. A variety of models were integrated to apportion the source of soil heavy metals, including positive matrix factorization (PMF), geographical detector (GD), eXtreme gradient boosting (XGBoost), and structural equation modeling (SEM). The result of PMF models revealed that there was collinearity between various heavy metals, and the same heavy metal may have a mixed source. The XGBoost model analysis indicated that there were significant non-linear relationships between soil heavy metals and source factors. A synergy between air quality and human activity factors was the key source of heavy metal that entered the study area, based on the results of the GD. Furthermore, the input path effect of heavy metals in the soil of the study area was quantified by SEM. The balance of evidence from the above models showed that air quality (SO2 and NO2) and factories in the study area had the greatest impacts on Cd, Cr, and Zn. Natural sources were dominant for Pb, while As, Cu, and Ni were contributed by soil parent material and factories. The above results led to the conclusion that there was a cycle path in the study area that continuously promoted the migration and accumulation of heavy metals in farmland soil; that is, the heavy metals discharged during oil exploitation and smelting entered the atmosphere and then accumulated in the farmland soil through precipitation, atmospheric deposition, and other paths. In this study, it is shown that a variety of models can be used to more comprehensively assess the sources of soil heavy metals. This approach can provide effective support for the rapid prevention and decision-making management of soil heavy metal pollution in coastal areas.

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Theoretical Study on Rock-Electric Characteristics of Complex Shaly Sandstones and its Application to Reservoir Saturation Evaluation - He Meng; Yueming Ye; Tangyan Liu; Shiqiong Liu; Cun Yang; Libao Wang (Natural Resources Research, 2023)

Flavor substances of low-valued red swamp crayfish (Procambarus clarkii) hydrolysates derived from double enzymatic systems - Chujun Li; Zongcai Tu; Wenyu Liu; Chunlin Wu; Yueming Hu; Hui Wang (Food Research International, 2023)

A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage - Fengjun Li; Youxia Shan; Haobin Wang; Guoxiang Jiang; Xiaochun Ding; Hanzhi Liang; Chunlan Wang; Xiangjin Kong; Lihong Xie; Yueming Jiang (Food Chemistry, 2023)

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

Decreasing Vulnerability of Storm Surge Disasters in Coastal Cities of China over the Past 30 Years - Dan Meng; Yueming Liu; Zhihua Wang; Xiaomei Yang; Xiaoliang Liu; Junyao Zhang; Ku Gao (Journal of Marine Science and Engineering, 2023)
From 2000 to 2020, storm surges occurred 397 times in China, resulting in direct economic losses of up to CNY 220.64 billion. Storm surges not only threaten safety but also cause property damage; hence, it is necessary to assess the changes in vulnerability to storm surges in order to understand how to reduce said vulnerability. Fifteen coastal cities of four types were chosen, with different levels of urban development, rapid expansion of impervious surface, high extent of agricultural land, and high fishery output value. Viewing vulnerability through the dimensions of exposure, sensitivity, and adaptability, a GIS and RS were used to evaluate and assess the vulnerability in 15 coastal cities in China over the past 30 years. The results indicated that the vulnerability of these 15 Chinese cities presented the characteristics of a continuous downward trend from 1990 to 2020, and the average rate of reduction in vulnerability over the 10 years from 2005 to 2015 was the highest, at 2.23%. The areas of high vulnerability shifted from the southern region to the northern region. The vulnerabilities in the southern region, with Shanghai, Shenzhen, and Dongguan, changed significantly, to 3.30%, 3.20%, and 3.45%, respectively. An important factor in determining vulnerability reductions is a city’s ability to adapt to storm surges. Coastal cities can improve their adaptability to storm surge disasters through general public budget expenditure, investment in fixed assets, GDP, and medical and health services, thereby alleviating their vulnerability. Due to China’s frequent storm surge disasters during the 2005–2015 period, government departments have strengthened the investment of relevant resources in adaptive indicators, ultimately causing the cities’ vulnerability to rapidly decrease during this period.

Co-60 gamma irradiation induced ovalbumin-glucose glycation and allergenicity reduction revealed by high-resolution mass spectrometry and ELISA assay - Guang-xian Liu; Zong-cai Tu; Hui Wang; Yueming Hu; Wen-hua Yang (Food Chemistry, 2023)

ZnS quantum dots implanted polyaniline-wrapped corn straw catalysts for efficient photocatalytic nitrate reduction without external addition of hole scavengers - Shuo Wang; Ying Zhao; Jing Feng; Tong Wei; Jun Ma; Yueming Ren; Chengying Bai (Chemical Engineering Journal, 2023)

DEM-CFD investigation on the effects of angularity and roughness on the mass loss of soil rock mixtures - Fan Chen; Yingchao Wang; Wen Jiang; Yin Guo; Yueming Wang (European Journal of Environmental and Civil Engineering, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

Functional traits and stand factors as strong drivers of radial growth response to hotter drought in a temperate forest of North China - Xuemei Wang; Kai Xu; Wenhao Miao; Linhao Gao; Saif Ullah; Yueming Lyu; Xiangping Wang (European Journal of Forest Research, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Spatiotemporal dynamics and influencing factors of the global material footprint - Heming Wang; Yao Wei; Yueming Wu; Xinzhe Wang; Yao Wang; Guoqiang Wang; Qiang Yue (Environmental Science and Pollution Research, 2022)

Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Shengpeng Li; Ruyue Wang; Yueming Jiang; Yanyu Li; Lin Zhu; Jianfeng Feng (Frontiers in Marine Science, 2022)
The last 30 years have witnessed the degradation and loss of function in the ecosystem of the Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of the Bohai Sea in recent years. In this study, we examined the seasonal variation of food webs in artificial reefs of Juehua Island by the Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency, and ecosystem maturity have increased from summer to autumn. However, the food web stability of artificial reefs has no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton, and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. This study suggests that stability is a more robust indicator for ecosystem assessment and could provide useful information in future restoration plans of the marine ecosystem.

A superpixel region merging based nonuniformity correction method for hyperspectral images - Xiaoyu Cheng; Zhouyin Cai; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Estimation of forest aboveground biomass by using mixed-effects model - Haoning Feng; Qi Chen; Yueming Hu; Zhiguo Du; Guantu Lin; Changwei Wang; Youju Huang (International Journal of Remote Sensing, 2021)

A spatial-spectral clustering-based algorithm for endmember extraction and hyperspectral unmixing - Xiaoyu Cheng; Zhouyin Cai; Jia Li; Maoxing Wen; Yueming Wang; Dan Zeng (International Journal of Remote Sensing, 2021)

Spatial effects of carbon emission intensity and regional development in China - Yingdong Wang; Yueming Zheng (Environmental Science and Pollution Research, 2021)

The effects of misregistration between hyperspectral and panchromatic images on linear spectral unmixing - Xiaoyu Cheng; Yueming Wang; Jianxin Jia; Maoxing Wen; Rong Shu; Jianyu Wang (International Journal of Remote Sensing, 2020)

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Effect of aluminate content in cement on the long-term sulfate resistance of cement stabilized sand - Kaiwei Liu; Yueming Wang; Ning-Jun Jiang; Aiguo Wang; Daosheng Sun; Xingxing Chen (Marine Georesources & Geotechnology, 2020)

Research on a novel extraction method using Deep Learning based on GF-2 images for aquaculture areas - Bo Cheng; Chenbin Liang; Xunan Liu; Yueming Liu; Xiaoxiao Ma; Guizhou Wang (International Journal of Remote Sensing, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Cholesterol 25-hydroxylase suppresses rabies virus infection by inhibiting viral entry - Yueming Yuan; Zongmei Wang; Bin Tian; Ming Zhou; Zhen F. Fu; Ling Zhao (Archives of Virology, 2019)

Aquaculture area extraction and vulnerability assessment in Sanduao based on richer convolutional features network model - Yueming Liu; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Fengshuo Yang (Journal of Oceanology and Limnology, 2019)

Object-based classification of cloudy coastal areas using medium-resolution optical and SAR images for vulnerability assessment of marine disaster - Fengshuo Yang; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Yueming Liu (Journal of Oceanology and Limnology, 2019)

Detection of short-term urban land use changes by combining SAR time series images and spectral angle mapping - Zhuokun Pan; Yueming Hu; Guangxing Wang (Frontiers of Earth Science, 2019)

Long-term exposure to low level of fluoride induces apoptosis via p53 pathway in lymphocytes of aluminum smelter workers - Pingjing Wen; Xiaomin Wei; Guiqiang Liang; Yanfei Wang; Yiping Yang; Lilin Qin; Weiyi Pang; Guangqiu Qin; Hai Li; Yueming Jiang; Qijun Wu (Environmental Science and Pollution Research, 2019)

Crop resistant starch and genetic improvement: a review of recent advances - Jian Xia; Dong Zhu; Ruomei Wang; Yue Cui; Yueming Yan (Theoretical and Applied Genetics, 2018)

Increased associated effects of topography and litter and soil nutrients on soil enzyme activities and microbial biomass along vegetation successions in karst ecosystem, southwestern China - Fujing Pan; Wei Zhang; Yueming Liang; Shujuan Liu; Kelin Wang (Environmental Science and Pollution Research, 2018)

Estimation of net primary productivity of forests by modified CASA models and remotely sensed data - Zhenhua Liu; Manqin Hu; Yueming Hu; Guangxing Wang (International Journal of Remote Sensing, 2018)

A global survey of bacterial type III secretion systems and their effectors - Yueming Hu; He Huang; Xi Cheng; Xingsheng Shu; Aaron P. White; John Stavrinides; Wolfgang Köster; Guoqiang Zhu; Zhendong Zhao; Yejun Wang (Environmental Microbiology, 2017)
Summary The type III secretion system (T3SS) is an important genetic determinant that mediates interactions between Gram‐negative bacteria and their eukaryotic hosts. Our understanding of the T3SS continues to expand, yet the availability of new bacterial genomes prompts questions about its diversity, distribution and evolution. Through a comprehensive survey of ∼20 000 bacterial genomes, we identified 174 non‐redundant T3SSs from 109 genera and 5 phyla. Many of the bacteria are environmental strains that have not been reported to interact with eukaryotic hosts, while several species groups carry multiple T3SSs. Four ultra‐conserved Microsynteny Blocks (MSBs) were defined within the T3SSs, facilitating comprehensive clustering of the T3SSs into 13 major categories, and establishing the largest diversity of T3SSs to date. We subsequently extended our search to identify type III effectors, resulting in 8740 candidate effectors. Lastly, an analysis of the key transcriptional regulators and circuits for the T3SS families revealed that low‐level T3SS regulators were more conserved than higher‐level regulators. This comprehensive analysis of the T3SSs and their protein effectors provides new insight into the diversity of systems used to facilitate host‐bacterial interactions.

The Caledonian paleokarstification of Longwangmiao Formation, Lower Cambrian in the central Sichuan basin, China - Xuefei Yang; Xingzhi Wang; Hao Tang; Yueming Yang; Jirong Xie; Wenjun Luo; Lincheng Dai (Carbonates and Evaporites, 2017)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)

Dolomitization by penesaline sea water in Early Cambrian Longwangmiao Formation, central Sichuan Basin, China - Xuefei Yang; Hao Tang; Xingzhi Wang; Yaping Wang; Yueming Yang (Journal of Earth Science, 2017)

Characterization of re-grown floc size and structure: effect of mixing conditions during floc growth, breakage and re-growth process - Jun Nan; Zhenbei Wang; Meng Yao; Yueming Yang; Xiaofei Zhang (Environmental Science and Pollution Research, 2016)

Reservoir characteristics and main controlling factors of the Longwangmiao Formation in the Moxi area, central Sichuan Basin, China - Xuefei Yang; Xingzhi Wang; Hao Tang; Yueming Yang; Jirong Xie; Wenjun Luo; Nan Jiang (Arabian Journal of Geosciences, 2016)

Molecular cloning and potential function prediction of homologous SOC1 genes in tree peony - Shunli Wang; Margherita Beruto; Jingqi Xue; Fuyong Zhu; Chuanjiao Liu; Yueming Yan; Xiuxin Zhang (Plant Cell Reports, 2015)

Selection of surfactant in remediation of DDT-contaminated soil by comparison of surfactant effectiveness - Ping Guo; Weiwei Chen; Yueming Li; Tao Chen; Linhui Li; Guanzhu Wang (Environmental Science and Pollution Research, 2014)

Removal of heavy metal ions from wastewater by a novel HEA/AMPS copolymer hydrogel: preparation, characterization, and mechanism - Zhengkui Li; Yueming Wang; Ningmei Wu; Qichun Chen; Kai Wu (Environmental Science and Pollution Research, 2013)

Molecular characterization and dynamic expression patterns of two types of γ-gliadin genes from Aegilops and Triticum species - Shunli Wang; Xixi Shen; Pei Ge; Jie Li; Saminathan Subburaj; Xiaohui Li; F. J. Zeller; S. L. K. Hsam; Yueming Yan (Theoretical and Applied Genetics, 2012)

Phylogenetic relationship of a new class of LMW-GS genes in the M genome of Aegilops comosa - Ke Wang; Liyan Gao; Shunli Wang; Yanzhen Zhang; Xiaohui Li; Miaoyi Zhang; Zhenze Xie; Yueming Yan; Matthew Belgard; Wujun Ma (Theoretical and Applied Genetics, 2011)

Molecular characterization of the celiac disease epitope domains in α-gliadin genes in Aegilops tauschii and hexaploid wheats (Triticum aestivum L.) - Zhenze Xie; Congyan Wang; Ke Wang; Shunli Wang; Xiaohui Li; Zhao Zhang; Wujun Ma; Yueming Yan (Theoretical and Applied Genetics, 2010)

Paleogene-Neogene stratigraphic realm and sedimentary sequence of the Qinghai-Tibet Plateau and their response to uplift of the plateau - KeXin Zhang; GuoCan Wang; JunLiang Ji; ManSheng Luo; XiaoHu Kou; YueMing Wang; YaDong Xu; FenNing Chen; RuiMing Chen; BoWen Song; JianYu Zhang; YinPing Liang (Science China Earth Sciences, 2010)

Overexpression and characterization of a thermostable trehalose synthase from Meiothermus ruber - Yueming Zhu; Dongsheng Wei; Jun Zhang; Yufan Wang; Hengyi Xu; Laijun Xing; Mingchun Li (Extremophiles, 2010)

Cloning and characterization of a novel low molecular weight glutenin subunit gene at the Glu-A3 locus from wild emmer wheat (Triticum turgidum L. var. dicoccoides) - Xiaohui Li; Aili Wang; Yinghua Xiao; Yueming Yan; Zhonghu He; Rudi Appels; Wujun Ma; S. L. K. Hsam; F. J. Zeller (Euphytica, 2008)

Berechnung von Temperatur- und Spannungszuständen in RCC-Staumauern - Yueming Zhu; Stephan Semprich; Yuefeng Ma; Weimin Cao; Hong Wang (WASSERWIRTSCHAFT, 2007)

On paleodrainage evolution in mid-late Epipleistocene based on radar remote sensing in northeastern Ejin Banner, Inner Mongolia - Wang Xinyuan; Guo Huadong; Chang Yueming; Zha Liangsong (Journal of Geographical Sciences, 2004)